Cinema and religion (Eurasian Journal of Philology Science and Education, 2015)
This publication is dedicated for a role of religion in a history of cinema. by analyzing As a result creator shows, how cinema comes like an instrument for a demonstration the religious value. And also that in the cinema keeps intimate content and a cognition of spirituality. Considered unique properties of cinema, manipulating by each, but the most important thing, is a quality of this cinema was a impulsing for a making talented cinematographic films, inside each was theme of spirituality and moral.
Keywords: creativity; cultural wealth; religion; film; cinema; the spectator; director